Making summer matter: The impact of youth employment on academic performance. Issue 2 (13th May 2021) - Schwartz, Amy Ellen; Leos‐Urbel, Jacob; McMurry, Joel; Wiswall, Matthew
Abstract : This paper examines New York City's Summer Youth Employment Program (SYEP). SYEP provides jobs to youth ages 14–24, and due to high demand for summer jobs, allocates slots through a random lottery system. We match student‐level data from the SYEP program with educational records from the NYC Department of Education and use the random lottery to estimate the effects of SYEP participation on a number of academic outcomes, including test taking and performance. We find that SYEP participation has positive impacts on student academic outcomes, and these effects are particularly large for students who participate in SYEP multiple times.